2011
DOI: 10.1155/2011/674968
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide in Cystic Fibrosis: A Potential New Target for Therapeutic Intervention

Abstract: Patients with cystic fibrosis (CF) are afflicted with many symptoms but the greatest challenge is the fight against chronic bacterial infections, leading to decreased lung function and ultimately death. Our group has recently found reduced levels of ceramides in CF patients and mice. Ceramides are sphingolipids involved in the structure of cell membranes but also participate in the inflammatory response, in cell signalling through membrane microdomains (lipid rafts), and in apoptosis. These characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 101 publications
0
16
0
Order By: Relevance
“…The role of sphingolipids in CF lung disease is incompletely understood. Most of the focus has centered on CF-related changes in membrane-bound ceramides (48). Our study points to a role for sphingolipid mediators.…”
Section: Discussionmentioning
confidence: 72%
“…The role of sphingolipids in CF lung disease is incompletely understood. Most of the focus has centered on CF-related changes in membrane-bound ceramides (48). Our study points to a role for sphingolipid mediators.…”
Section: Discussionmentioning
confidence: 72%
“…Other investigators have reported a deficiency of ceramide in CF cells and associated this deficiency with an intense lung inflammatory response [31]. Clinical trials of fenretinide to increase CF cell ceramide levels and decrease lung disease in CF patients are currently being developed [31][32][33]. The objectives of these studies are clearly opposite.…”
Section: Lipid Abnormalitiesmentioning
confidence: 99%
“…Annexin 1 is a potent PLA 2 and Cox 2 inhibitor [64]. Although the study results in CF concerning ceramides, important for phagocytosis [65], are not unequivocal, the associations to the plasma fatty acid pattern as well as to the CFTR mutations are interesting [66,67], especially since CF patients are known to display defective pseudomonas internalization [68]. The importance of these pathways in CF have further been demonstrated by Radzioch et al showing a normalization of LCPUFA and ceramide levels in CF mice by giving fenrenitide, a IL-1 β inhibiting retinoid, which interferes with the ceramide transformations [66,69].…”
Section: Etiology Of Fatty Acid Disturbancesmentioning
confidence: 99%